PERANAN NOTARIS DALAM PROSES PERADILAN KAITANNYA DENGAN KEWAJIBAN MENJAGA KERAHASIAAN JABATAN DI KOTA SAMARINDA - Iin Noviyanti (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
Abstract      Law No. 30 of 2004 concerning Notary, is expected to provide better legal protection to the community or to the Notary itself. A Notary as an officer, is a place for someone to be able to obtain advice that can be relied upon.      In addition to creating an authentic deed, a notary is also obliged directly or indirectly to maintain smooth proceedings occur, including with regard to the judicial process, both in the criminal and civil justice.      Notary according to the law, should not take sides, it means that the notary in helping the parties to formulate in deed, must consider the interests of both parties and should keep that relate to the content deed made. Especially in case of a dispute between the two sides, which resulted in the investigation of the notarial deed.      It should be for all parties, both investigators, prosecutors, and judges can respect, uphold the oath of office, official secret, and the right of refusal held by a notary, and should be able to work together well and remained firm on their Code of Conduct in every profession there except for the notary profession though. Given these efforts, it is expected as part of efforts to enforce the law and is also expected to positively impact the law enforcement itself.